Impacto do armazenamento a curto prazo e de múltiplos ciclos de congelamento/descongelamento sobre as concentrações séricas de ferro, ferritina e transferrina - Klat, Rogério Luciano (2020)
Most changes in laboratory results, despite all the care taken to eliminate or minimize them, occur due to processes related to the pre-analytical phase. This stage may suffer interference, such as: time and temperature of storage of the samples for later analysis, submission of the samples to freeze/thaw cycles, among others, which may result in a reduction of the stability of the sample to be analyzed. As there are no short-term stability studies exploring iron status, this study aims to investigate the effects of freezing and thawing cycles on serum iron, transferrin and ferritin, as well as the impact of short-term storage on stability of these analytes. Serum samples from ten volunteers were subjected to three consecutive freezing cycles at -20°C and -80°C and thawing at 37°C on the same day. Serum aliquots were also kept at 4°C, -20°C and -80°C for twenty-eight days. Iron, ferritin and transferrin were measured after one, seven, fourteen, twenty-one or twenty-eight days of storage. Serum ferritin and transferrin varied from -2.6 to 2.6% and -1.7 to 2.4%, respectively, in their concentrations during the three freezing and thawing cycles at -20°C and -80°C, however, the variations were statistically significant only at -20°C (P=0.003 and P=0.002, respectively). No significant changes were found for iron at both temperatures. Storage at 4°C, -20°C and -80°C for up to four weeks significantly affected serum iron, ferritin and transferrin concentrations (P<0.01 for all). Due to the fact that iron, ferritin and transferrin were affected by the storage of samples at temperatures of 4°C, -20°C and -80°C for up to four weeks, and the freezing and thawing cycles at -20°C influenced the measurement of serum ferritin and transferrin, it is recommended, whenever possible, that iron status analytes be determined in fresh samples.